2019
DOI: 10.3390/cells9010078
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Potential of Bone Marrow Derived CD133+ and CD271+ Intramyocardial Stem Cell Trans- Plantation Post MI

Abstract: Background: Bone marrow (BM)-derived stem cells with their various functions and characteristics have become a well-recognized source for the cell-based therapies. However, knowledge on their therapeutic potential and the shortage for a cross-link between distinct BM-derived stem cells, primed after the onset of myocardial infarction (MI), seems to be still rudimentary. Therefore, the post-examination of the therapeutic characteristics of such primed hematopoietic CD133+ and mesenchymal CD271+ stem cells was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…We detected CD271 + subpopulations in adult MSC [24,26]. Similar to us, others have reported that all fibroblast colony-forming cells (CFU-F) in human BM are present and rare [38,39].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We detected CD271 + subpopulations in adult MSC [24,26]. Similar to us, others have reported that all fibroblast colony-forming cells (CFU-F) in human BM are present and rare [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to us, others have reported that all fibroblast colony-forming cells (CFU-F) in human BM are present and rare [38,39]. While the total number of the MACS-purified CD271 + from sternal BM accounted approx.~5500 per mL of the aspirate [26] in our study, the iliac crest BM aspirate accounted in 2-2.5 fold more MSC progenitors ranging from 1000-15,000 per mL of aspirate [38,40]. Hence, those studies have evidenced a linear relationship between numbers of mononuclear cells and mesenchymal progenitor cells as well as positive correlation between these mesenchymal progenitors and CFU-F counts.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although we couldn't con rm myogenic differentiation of MSCs themselves in this study, IL-10 is also thought to play a role in the long-term engraftment and survival of MSCs in muscle tissue, resulting from association with surrounding myogenic stem/progenitor cell populations, such as satellite cells, skeletal muscle-MSCs, and broadipogenic progenitors (FAB) for muscle repair. Furthermore, myocardial infarction with CD271 + bonemarrow MSCs lowered expression of in ammatory cytokines and signi cantly increased pro-angiogenic VEGF [37]. CD271 + MSCs expressing IL-10 are also thought to enhance pro-angiogenic differentiation in injured tissue as a result of prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
“…Bone regeneration comprises a series of complex and continuous physiological processes that can be divided into four stages: haematoma formation, fibrous callus formation, bone callus formation and bone shaping plus remodelling 7 . Numerous studies have shown that inflammatory responses and neovascularization are key factors for initiation of bone regeneration 8‐10 . Hausman et al 11 demonstrated that application of angiogenesis inhibitors to a rat model of femoral fracture inhibited fracture healing and led to atrophic nonunion.…”
Section: Introductionmentioning
confidence: 99%